The Concept of Affordances in Applied Linguistics and Multilingualism (Eurasian Scientific Herald, 2023)
In this article the line of inquire about on the concept of affordances in connected etymology and humanism of dialect will be analyzed, which David Singleton has examined in later a long time (Singleton and Aronin 2007; Aronin and Singleton 2010, 2012a, 2012b; Singleton et al. 2013). The concept of affordances in reference to connected phonetics and multilingualism stimulates intrigued, but thinks about are still rare on the ground. The reason of this chapter is to outline the past hypothetical understanding of affordances, and to extend the point of view encourage. Along side laying out the importance of this concept for dialect educating, learning and utilize, the chapter will recommend extra down to earth ways of capitalizing on our understanding of affordances, and see into one specific kind of affordance which fabric culture offers to dialect learners, instructors and speakers.